Seismic performance of dry-friction energy dissipation devices in shear-frame buildings - Patro, Sanjaya Kumar; Sinha, Ravi (Journal of Structural Engineering, 2025)
In recent years the applications of friction-based passive energy dissipation devices have been found to be very effective in reducing structural response to earthquake excitations. These systems have been implemented for a large number of buildings. In state-of-the-practice, the hysteretic behavior of dry-friction energy dissipation devices has been typically modeled with Coulomb friction having a constant coefficient of friction. However, the basic laws for typical sliding materials and experimental investigations show non-linear relationship between friction and sliding velocity, which includes stiction and Stribeck effect. The influence of stiction and Stribeck effect may be significant and can not be ignored in simulating the dynamic responses of structures with friction-based energy dissipation devices. In this paper the optimal performance of frame buildings with dry-friction devices has been investigated. Since buildings with friction devices behave in a highly nonlinear manner, nonlinear response-history analysis considering comprehensive sliding friction models has been carried out. Different performance indices have been used to quantify the influence of the device properties.